Association Between Severity of Leptospirosis and Subsequent Major Autoimmune Diseases: A Nationwide Observational Cohort Study - Chen, Chih-Chung; Hung, Yao-Min; Chiu, Lu-Ting; Chou, Mei-Chia; Chang, Renin; Wei, James Cheng-Chung (Frontiers in Immunology, 2021)
Introduction: Infections play a role in autoimmune diseases (AD). Leptospirosis has been linked to trigger systemic lupus erythematosus. Objective: To investigate subsequent risk of major AD in hospitalized Taiwanese for Leptospirosis. Methods: Retrospective observational cohort study. The enrolled period was from 2000 to 2012. In the main model, we extracted 4026 inpatients with leptospirosis from the Taiwan National Health Insurance Research Database (NHIRD), and 16104 participants without leptospirosis at a 1:4 ratio propensity-score matched (PSM) by age, gender, index year, and comorbidities. The follow-up period was defined as the time from the initial diagnosis of leptospirosis to major AD occurrence or 2013. This study was re-analyzed by frequency-matching as a sensitivity analysis for cross-validation. Univariable and multivariable Cox proportional hazards regression models were applied to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: The adjusted HR (95% CI) of major ADs for the leptospirosis group was 4.45 (3.25-6.79) (p<0.001) compared to the controls after full adjustment. The risk of major ADs was 5.52-fold (95% CI, 3.82-7.99) higher in leptospirosis patients hospitalized for seven days and above than the controls, while 2.80-fold (95% CI, 1.68-5.61) in those hospitalized less than seven days. The sensitivity analysis yields consistent finding. Stratified analysis revealed that the association between leptospirosis and major ADs was generalized in both genders, and all age groups. Conclusions: Symptomatic leptospirosis is associated with increased rate of subsequent major ADs, and the risk seems to be higher in severe cases.